MODAL SOSIAL DALAM PEKOPERASIAN DI INDONESIA : TINJAUAN STUDI LITERATURE REVIEW - Ramdani, Mohammad Ilham; Ardiansyah, Hamdan; Setiawan, Agung (Politeknik Bisnis Indonesia, 2025)
This study explores the role of social capital in the development of cooperatives in Indonesia through a literature review approach. Cooperatives, as people-oriented economic entities, rely heavily on values of trust, solidarity, and democratic participation, which are key components of social capital. The dual identity of cooperative members—as both owners and users—fosters mutual responsibility and internal cohesion, strengthening decision-making and operational collaboration. However, modern challenges have led to a decline in social capital, including reduced member involvement and increased corporatization, threatening the cooperative's foundational values.Using a qualitative descriptive method with document analysis, this research examines theoretical frameworks of social capital from scholars such as Bourdieu, Coleman, and Putnam, and relates these to the dynamics within cooperatives. The findings indicate that social capital— bonding, bridging, and linking—plays a vital role in supporting cooperative sustainability and social welfare. Strengthening these networks is essential not only for cooperative performance but also for broader community development. This paper highlights the need for cooperative governance that is rooted in trust, member participation, and inclusive social structures to maintain relevance in an evolving economic landscape.